Waves off Gopalpur, northern Bay of Bengal during Cyclone Phailin - M. M. Amrutha; V. Sanil Kumar; T. R. Anoop; T. M. Balakrishnan Nair; A. Nherakkol; C. Jeyakumar (Annales Geophysicae, 2014)
The wave statistical parameters during Cyclone Phailin which crossed the northern Bay of Bengal are described based on the Directional Waverider buoy-measured wave data from 8 to 13 October 2013. On 12 October 2013, the cyclone passed within 70 km of the Waverider buoy location with a wind speed of 59.2 m s−1 (115 knots), and during this period, a maximum significant wave height of 7.3 m and a maximum wave height of 13.5 m were measured at 50 m water depth. Eight freak wave events are observed during the study period. The ratio of the maximum wave height to significant wave height recorded is found to be higher than the theoretical value and the ratio of the crest height to wave height during the cyclone was 0.6 to 0.7. The characteristics of the wave spectra before and after the cyclone is studied and found that the high-frequency face of the wave spectrum is proportional to f−3 before the cyclone and is between f−4 and f−5 during the cyclone period.